Let F(x)=x+3/x+1. The difference quotient for f(x) at x=a is defined f(a+h)-f(a)/h. For the given f, fully simplify the difference quotient
- print Print
- list Cite
Expert Answers
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
f(x) = x+3/ x+1
f(a) = a+3/a+1
f(a+h) = a+h+3/a+h+1
f(a+h) - f(a) /h = [(a+h+3)/(a+h+1) - (a+3/(a+1)]/h
= (a+h+3)(a+1) - (a+3)(a+h+1)/h(a+1)(a+h+1)
= (a^2 + 4a + ah + h + 3 - (a^2 + ah + 4a + 3h + 3)/h(a+1)(a+h+1)
= - 2h/(h(a+a)(a+h+1)
= -2/(a+1)(a+h+1)
Related Questions
- Evaluate the difference quotient for the given function. Simplify your answer. f(x) = 4 + 3x -...
- 1 Educator Answer
- For the function f(x) = 4 + 3x - x^2, determine (f(3+h) - f(3))/h and simplify the result.
- 2 Educator Answers
- If f(x)=x+4 and h(x)=4x-1, find a function g such that g(f(x)) = h(x).
- 2 Educator Answers
- Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
- 1 Educator Answer
- Let f(x) be the function `2x^2-10x+4` , the quotient `(f(10+h)-f(10))/h` can be simplified ah+b...
- 1 Educator Answer
F(x) = (x+3)/(x+1).
The given definition of difference coefficient d/dx f(x) = {f(a+h)-fa)}/h.
To find the difference coefficient for the given function F(x):
Diference coefficient F(x) at a is given by:
{F(a+h)-F(a)}/h = {(a+3+h)/(a+1+h) - (a+1)/(a+1)}/h.
F(x) = (x+3)/(x+1) = (x+1+2)/(x+1) = 1+2/(x+1)
Therefore { F(x+h)-F(x)}/h = {1 -1 +(2/(x+1+h) - 2/(x+1)}/h
={2 (x+1) - 2(x+1+h)}/[(x+1+h)(x+1)h]
= {2x+2 -2x-2-2h}/[(x+1+h)(x+1)h]
= -2h/[(x+1+h)(x+1)h]
= -2/(x+1+h)(x+1)
Student Answers